INNOVATIVE METHODS FOR TEACHING PRIMARY SCHOOL LEARNERS - Ibodullayeva Zilola, Usmanova Momagul (American Journals Publishing, 2023)
This article describes in detail the main tasks of teaching technology in general secondary educational institutions, improving the pedagogical mechanisms of teaching technology in primary schools based on the competency approach, and the main goal of teaching technology in general secondary educational institutions.
Keywords: science of technology, competence approach, pedagogical mechanism, intellectual ability, informative teaching.